Analysing public sentiment towards government policies in Singapore using SenticNet - Yap, Eugene (Nanyang Technological University, 2024)
This study uses SenticNet to analyse Reddit Singapore comments for sentiment analysis. The objective is to understand how the public feels about certain policies the Singapore government has proposed or implemented. The study reviews the mechanisms of SenticNet and the connection between sentiment analysis and policymaking. After visualising the data obtained from Sentic APIs, error analysis is performed on the misclassifications. In conclusion, most comments are critical of policies from both sides, indicating that people are more likely to think critically about policies than to accept them at face value.